Efforts to Improve Learning Outcomes and Motivation Through Experimental Learning on Dynamic Electricity - Isti Wulandani; Jeni Permatasari; Kholidah Zalfiyana; Khusniatus Shobikhah; Kristin Dwi Yulia Hartono; Dyah Astriani (Jurnal Ilmiah Profesi Pendidikan, 2025)
Motivation and learning outcomes are two interrelated aspects. A high level of learning motivation will result in commitment and resilience in learning, thereby leading students to improve their learning outcomes. This research aimed to describe the improvement of learning outcomes and student motivation after application experimental methods in science learning on the topic of dynamic electricity. This research is a type of Classroom Action Research design consisting of two cycles with instruments in the form of formative test sheets and questionnaires where there are 30 students as research subjects. Based on the results of the formative test in cycle I, an average score of 85.4 was obtained and increased to 88.7 in cycle II. The classical learning completion in cycle I was 53.3% and increased to 86.7% in cycle II. According to the questionnaire’s results, it is known that 100% of respondents thought that using experimental methods to teach science was very interesting and enjoyable. In addition, 83.3% of respondents stated that experimental methods can increase their motivation to learn on dynamic electrical materials. Consequently, it might be concluded that the application of experimental methods is significantly able to improve student learning outcomes and motivation.